ANALISIS PERSEPSI NELAYAN DALAM PENGELOLAAN SUMBERDAYA PERIKANAN BERKELANJUTAN DI TAMAN NASIONAL KARIMUNJAWA1 - M Mussadun; Achmad Fahrudin; Tridoyo Kusumastanto; M. Mukhlis Kamal (Diponegoro University, 2011)
The sustainable fisheries resources management at the Karimunjawa National Park (KNP) is a very complicated effort. One of the serious issues is that the national park was declared by government when it has been inhabited by fisherfolk community. It is therefore very important to find out fisherfolk perception on sustainable fisheries resources management within the KNP. In the present study, a model of fisherfolk perception on sustainable fisheries resources management at the KNP, which included: fisheries resources management, national park management, community participation, law enforcement, monitoring efforts, and technical- and policy- implementations. Analysis method used Structural Equation Modeling (SEM) with program analysis Lisrel 8.52. Total respondents surveyed were 189 fishermen.Results of model analysis SEM showed that fisherfolk perception on sustainable fisheries resources management at KNP expect: (1) surveillance efforts, (2) commitment on law enforcement, and (3) involvement of fisherfolk participation. Expected policies were (1) decentralization, (2) integrated approach, (3) balance proportion between welfare and conservation, (4) fair distribution of fish catch, and (5) regulation of market mechanism.